HUMAN CAPITAL IN THE CONDITIONS OF DIGITALIZATION OF UZBEKISTAN - Gaffarova Gulchehra Gulamjanovna; Berkinov Oybek Tokhir oglu; Yuldoshev Avazbek Abdurashid oglu (The Bioscan, 2024)
Human capital is the main factor in the modern socio-economic development. In particular, it is important for the innovative and intellectual development of the Republic of Uzbekistan. This becomes especially important during the transition to an innovative economic system and the active development of communication and information technologies, i.e. in the context of active digitalization of economic relations, their transformation towards the intangible sphere, the knowledge economy, the Internet of things, big data, cloud technologies, and so on. These changes require the implementation of innovative approaches to human capital management aimed at developing the economy of the government. The modern Uzbek society is raising to an innovative path of socio-economic development based on knowledge, and needs the highest level of human productive forces. Investments in science, education, the social sphere in modern economic conditions are of major socio-economic importance; contribute to the expanded reproduction and accumulation of human abilities, professional competencies and economic opportunities of the population. Nowadays, human capital is getting changed into the form of intellectual capital associated with the heuristic nature of new knowledge. And the younger generation is more becoming the bearer of modern intellectual capital, in which unique values, a new type of motivation, new forms of communication and new skills (including digital ones) are being actively formed. Surely, knowledge is becoming a vital component of human as a factor regulating and determining his life and activity. As owning the physical capital, human capital is also being formed, which is ‘becoming a decisive force in the development of society in the second half of the 20th century.’ Therefore, the purpose of the article is to provide a philosophical analysis of the impact of digitalization on human capital and its development. And also the factors of human capital development in the ongoing reforms in the country and in the process of digitization has been emphasized.